Analyzing User Interface on Adx International Website Using Heuristic Method and System Usability Scale (SUS) - Djuniasih, Putry Erica; Wijaya, Anugerah Bagus; Prasetyo, Agung (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Adx International is one of the international shipping services that has collaborated with various marketplaces. Along with the development of technology, Adx International chose a website as a promotional material as well as a system for the transaction process. This research will discuss problems with the UI/UX design of the website by distributing questionnaires to users. After that, several problems were found such as problems with navigation design (search filters), colors that are not aligned, excessive use of icons and there is no guidebook for using the Adx International website. Therefore, further user interface analysis is required. To evaluate the sustainability of this platform, a combination of Heuristic and System Usability Scale (SUS) methods are used in this research because the two methods have different but complementary focuses. Heuristic provides perspectives from experts or experts, while SUS provides perspectives from users. This research uses 10 heuristic aspects and 10 SUS questionnaire questions. The result of this study is to provide recommendations for improvement from both perspectives and identify aspects that need to be improved. The SUS score in this study for the Adx International website is 55. In addition, the results of this study present recommendations for design improvements from various aspects, therefore it can be concluded that this research is successful.